Patterns of occurrence and abundance in colony complexes of the mexican prairie dog (Cynomys Mexicanus) in productive and unproductive grasslands - Yeaton, Richard I.; Flores-Flores, José L. (Instituto de Ecología, A.C., 2006)
The Mexican prairie dog lives in a small (500-600 km2) area of northeastern Mexico. The species is listed as endangered due to habitat fragmentation from recent large-scale agricultural development in the northern part of its limited geographical range and from shrub encroachment in the south. In this work we aim to study the role of Mexican prairie dog in the ecology of grasslands in the southern Chihuahuan Desert. Most of the species’ colonies, particularly in the far south of its range, occur today in short grasslands that grow on low productivity, gypsum-derived soils where the rate of such shrub encroachment is reduced. A survey of the region surrounding these southern colonies indicated that this has not always been the case as evidence of the species’ occurrence on more productive alluvial soils in the past is apparent. Biomass production and seasonal prairie dog densities were measured on these low productivity soils in the south of its range and on richer and deeper alluvial soils to the north. Total biomass production was seven times greater and densities were three-and-one-half times greater on the deeper alluvial soils. Adult seasonal densities were not significantly different within a soil type during the period monitored while juvenile densities increased significantly in the summer censuses due to the birth of young. The similar seasonal densities at each site suggest that the Mexican prairie dog is resource limited. An inferential study of the development of one isolated colony on the more productive alluvial soils in the north of the species’ range showed lower prairie dog densities in the center of the colony and at the edge of the colony in the zone of recent expansion than in the area peripheral to the center. Vegetation coverage was too scarce in the center of the colony to quantify. The areas peripheral to the center and in the zone of expansion were reduced in coverage of grasses and sedges in comparison to the unutilized surrounding grassland while the palatable grass, Bouteloua gracilis, was absent in the center and periphery of the colony and increased significantly in coverage from the zone of expansion to the adjoining grassland.Such low productivity grasslands may have served as refuges for the species during previous episodes of shrub encroachment in the Holocene. In addition, the natural fragmentation of such grasslands suggested that the Mexican prairie dog might function as a metapopulation. Colonizations and extinctions were recorded at monitored areas on each soil type. The major difference between the two complexes was due to the greater productivity of the alluvial soils in the north. Consequently, three times as many young per hectare are produced on these soils, greatly increasing the probability of the species maintaining an extant colony or successfully founding new colonies there. The probability of extinction of the Mexican prairie dog is higher in the south of its range due to these lower densities and conservation of the species there should involve the systematic transplantation of individuals from colonies on the richer alluvial soils to the north.